Gallic acid attenuates hypertension, cardiac remodeling, and fibrosis in mice with NG-nitro-L-arginine methyl ester-induced hypertension via regulation of histone deacetylase 1 or histone deacetylase 2. Issue 7 (July 2017) - Jin, Li; Lin, Ming Quan; Piao, Zhe Hao; Cho, Jae Yeong; Kim, Gwi Ran; Choi, Sin Young; Ryu, Yuhee; Sun, Simei; Kee, Hae Jin; Jeong, Myung Ho
Abstract : Objective: Gallic acid, a natural chemical found in plants, has been reported to show antioxidant, anticancer, and anti-inflammatory effects. We investigated the efficacy of a short-term or long-term treatment with gallic acid in N G -nitro-L-arginine methyl ester (L-NAME)-induced hypertensive mice and the underlying regulatory mechanism. Methods: Hypertension was sufficiently induced after 2 weeks of L-NAME administration. Cardiac remodeling was assessed by echocardiography. Hypertrophic markers, transcription factors, and fibrosis-related gene expression were evaluated by quantitative real-time polymerase chain reaction and western blotting. Results: Gallic acid effectively lowered SBP, regardless of the administration route (intraperitoneal or oral). L-NAME increased the left ventricular (LV) thickness without an increase in the total heart weight. Weekly echocardiography demonstrated that gallic acid significantly reduced LV posterior wall and septum thickness in chronic L-NAME mice from 3 to 7 weeks. The administration of gallic acid to mice showed a dual preventive and therapeutic effect on the L-NAME-induced LV remodeling. The effect was associated with the suppression of the gene expression of hypertrophy markers and the GATA-binding factor 6 (GATA6) transcription factor. Short-term or long-term treatment with gallic acid attenuated cardiac fibrosis and reduced the expression of histone deacetylase 1 and 2 in H9c2 cells and in rat primary cardiac fibroblasts, as well as in vivo . Small interfering RNA knockdown confirmed the association of these enzymes with L-NAME-induced cardiac remodeling and fibrosis. Conclusion: These results suggested that gallic acid may be a potential therapeutic agent for the treatment of cardiovascular diseases with hypertension and cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text